Silicon-carbon composite negative electrode material and preparation method thereof
By introducing a porous carbon framework and indium powder to form a hybrid electron-ion conductor network in silicon-carbon composite anode material, the problems of volume expansion and lithium dendrite deposition in all-solid-state batteries are solved, achieving high efficiency in cycle stability and improved safety performance.
Patent Information
- Application Number
- CN202511208706.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-27
- Publication Date
- 2025-11-28
AI Technical Summary
Existing silicon-carbon composite anode materials suffer from volume expansion and lithium dendrite deposition issues in all-solid-state batteries, leading to mechanical fracture and battery capacity decay. In particular, rapid interface polarization under high-rate charging conditions limits their application.
A porous carbon framework structure is used to fill silicon particles and uniformly distributed indium powder on the surface to form a three-dimensional network of hybrid electron-ion conductors, thus constructing a silicon-carbon composite anode material. The high ductility and high mechanical toughness of indium alleviate volume expansion and lithium dendrite formation.
It significantly improves the cycle stability and safety performance of the battery. The silicon-carbon composite anode material retains 100% capacity after 500 cycles, while the traditional material only retains 67%, and it also inhibits the formation and deposition of lithium dendrites.
Smart Images

Figure CN121035181A_ABST
Abstract
Description
Technical Field
[0001] This specification relates to the field of solid-state batteries, specifically to a silicon-carbon composite anode material, its preparation method, and solid-state batteries using this anode material. Background Technology
[0002] With the rapid development of electronic devices, lithium-ion batteries, as an important energy storage device, have attracted widespread attention for performance improvement. Among lithium-ion battery anode materials, silicon-based materials are considered one of the most promising next-generation anode materials due to their high theoretical capacity.
[0003] However, existing silicon-carbon composite anode materials still have the following problems: First, in all-solid-state batteries, the rigid solid-solid interface imposes severe mechanical constraints, leading to a strong electrochemical-mechanical coupling effect. This makes the volume expansion (up to 300%) of the silicon anode during lithiation more prominent, easily causing mechanical fracture of the material and capacity decay of the battery. Second, existing technologies mainly focus on solving the volume expansion problem of silicon anodes, but do not adequately consider the risk of lithium dendrite formation in all-solid-state batteries. Especially under high-rate charging conditions, the rapid polarization of the solid electrolyte layer at the interface will cause lithium to be deposited in the silicon / carbon anode under a highly lithiated state, resulting in a sharp drop in overpotential and potentially inducing dendrite deposition at the interface. This severely limits the practical application of silicon-based anode materials in all-solid-state batteries.
[0004] Therefore, there is an urgent need to develop a new type of silicon-carbon composite anode material that can simultaneously solve the problems of volume expansion and lithium dendrite formation in silicon anodes in all-solid-state batteries, especially the problem of lithium dendrite deposition and growth, thereby improving the cycle stability and safety performance of the battery. Summary of the Invention
[0005] To address the issues of volume expansion of silicon anodes and lithium dendrite deposition and growth at the interface caused by rigid solid-solid interfaces in all-solid-state batteries, this specification provides a silicon-carbon composite anode material constructed by forming a three-dimensional network of hybrid electron-ion conductors with indium, porous carbon framework, and silicon particles.
[0006] The technical solution adopted by this specification to solve its technical problem is: to provide a silicon-carbon composite anode material, including a porous carbon skeleton structure, silicon particles filling the pores of the porous carbon skeleton structure, and indium powder approximately uniformly distributed on the surface of the porous carbon skeleton structure.
[0007] Furthermore, the particle size of the silicon particles is 5-200 nm.
[0008] Furthermore, the indium powder has a particle size of less than 100 nm.
[0009] Furthermore, the porous carbon framework structure, the silicon particles, and the indium powder form a porous three-dimensional hybrid electron-ion conductor (MIEC) network.
[0010] This specification also provides a method for preparing a silicon-carbon composite anode material, comprising: preparing porous silicon-carbon based on a porous carbon framework and a silicon source; mixing the porous silicon-carbon and indium powder in a preset ratio and stirring; adding a binder and a solvent, mixing to form a slurry, and stirring the slurry; coating the stirred slurry onto a substrate and drying it to obtain the silicon-carbon composite anode material.
[0011] Preferably, the indium powder accounts for 0.5-3% of the total mass.
[0012] Preferably, after mixing and stirring the porous silicon carbide and the indium powder, the process further includes: ball milling for a preset time, wherein the preset time is 0.5-1.5 hours.
[0013] Preferably, the drying temperature is 100-160°C.
[0014] Preferably, the adhesive accounts for 0.3%-0.8% of the total mass.
[0015] This specification also provides a solid-state battery, including the aforementioned silicon-carbon composite anode material.
[0016] The beneficial effects of this instruction manual are as follows:
[0017] 1. By introducing indium onto the porous silicon-carbon surface, a three-dimensional network of hybrid electron-ion conductors is formed, effectively suppressing the formation and deposition of lithium dendrites. Indium's high ductility endows the silicon-carbon anode with higher lithium diffusion and strain tolerance. Indium enriches at the porous structure interface, promoting uniform lithium nucleation at the porous framework interface and preventing local lithium accumulation. At the same time, the highly mechanically tough indium-rich interface reduces stress accumulation during lithiation / delithiation, maintaining the interface consistency between the electrode and the electrolyte.
[0018] 2. The porous three-dimensional MIEC network constructed in this specification can effectively alleviate the volume expansion effect of silicon anodes during charging and discharging. The introduction of indium optimizes the diffusion rate of lithium ions in the anode and reduces the expansion problem of silicon materials. The porous three-dimensional MIEC network has a better buffering effect during lithium ion insertion / extraction, and significantly improves structural stability.
[0019] 3. Compared with existing technologies, the silicon-carbon composite anode material described in this specification maintains 100% capacity retention after 500 cycles, while existing silicon-carbon anodes experience capacity decay to 67% after 500 cycles. The silicon-carbon composite anode material described in this specification exhibits excellent cycle stability and high-efficiency charge-discharge capability, significantly improving battery performance. Attached Figure Description
[0020] To more clearly illustrate the technical solutions of the embodiments of this specification, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of this specification and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 This is a flowchart of the preparation method of the silicon-carbon composite anode material described in the embodiments of this specification.
[0022] Figure 2 This is a SEM image of the silicon-carbon composite anode material described in the embodiments of this specification.
[0023] Figure 3 This is a comparison of the electrochemical performance test results of existing silicon-carbon anode materials and the silicon-carbon composite anode materials described in the embodiments of this specification when applied to solid-state lithium batteries.
[0024] Figure 4 This is a comparison of cross-sectional SEM images of existing silicon-carbon anode materials and the silicon-carbon composite anode materials described in the embodiments of this specification when applied to solid-state lithium batteries.
[0025] Figure 5 This is a top-view SEM image comparison of existing silicon-carbon anode materials and the silicon-carbon composite anode materials described in the embodiments of this specification when applied to solid-state lithium batteries. Detailed Implementation
[0026] The technical solutions of this specification will now be clearly and completely described with reference to the accompanying drawings and embodiments. Obviously, the described embodiments are merely some, not all, of the embodiments described herein. All other embodiments obtained by those skilled in the art based on the embodiments of this specification without creative effort are within the scope of protection of this specification.
[0027] It should be noted that similar or identical parts are referred to by the same reference numerals in the accompanying drawings or description. Implementations not shown or described in the drawings are those known to those skilled in the art. In this specification, terms such as "first" and "second" are used only to distinguish descriptions and should not be construed as indicating or implying relative importance. Furthermore, the term "comprising" will be used in the embodiments of this specification to indicate the presence of a feature subsequently stated, but does not preclude the addition of other features.
[0028] Figure 1 This is a flowchart illustrating the preparation method of the silicon-carbon composite anode material described in the embodiments of this specification. Figure 1 As shown, the preparation method of silicon-carbon composite anode material includes the following steps:
[0029] Step 110: Prepare porous silicon carbon based on a porous carbon framework and a silicon source.
[0030] In this specification, the porous carbon framework possesses an abundant pore structure. The pore structure of the porous carbon framework is similar to a honeycomb structure. In some embodiments, the porous carbon framework may be prepared using existing materials or by a hydrothermal method, and this specification does not limit this.
[0031] In some embodiments, chemical vapor deposition can be used to place the porous carbon framework structure in a reaction chamber, introduce SiH4 gas as a silicon source, and allow silicon atoms to be deposited and grown in the pores of the porous carbon framework structure.
[0032] In some embodiments, silicon particles of suitable size can be obtained by controlling the reaction temperature and time. The particle size of the silicon particles affects the performance of the subsequently prepared silicon-carbon composite anode material. For example, if the particle size of the silicon particles is too large, it may damage the carbon skeleton and result in limited expansion space; if the particle size is too small, it may result in small gaps between the particles or even close contact between them, further leading to failure due to lack of expansion space during charging and discharging.
[0033] In some embodiments, the silicon particles have a particle size of 5-200 nm. In some embodiments, the silicon particles have a particle size of 8-180 nm. In some embodiments, the silicon particles have a particle size of 10-150 nm. In some embodiments, the silicon particles have a particle size of 15-100 nm. In some embodiments, the silicon particles have a particle size of 20-100 nm. In some embodiments, the silicon particles have a particle size of 30-80 nm.
[0034] Step 120: Mix the porous silicon carbide and indium powders in a preset ratio and stir.
[0035] Specifically, porous silicon carbide and indium powder are mixed in a certain proportion and stirred until homogeneous. Then, the homogeneous mixture is added to a ball mill and milled for a preset time.
[0036] In some embodiments, the amount of indium powder added needs to be controlled to ensure the performance of the subsequently prepared silicon-carbon composite anode. If the amount of indium added is too large, it can easily lead to a short circuit inside the battery; if the amount of indium added is too small, the effect of suppressing lithium dendrites will be weakened.
[0037] In some embodiments, the indium powder comprises 0.5-3% by mass. In some embodiments, the indium powder comprises 0.6-2.8% by mass. In some embodiments, the indium powder comprises 0.7-2.7% by mass. In some embodiments, the indium powder comprises 0.8-2.6% by mass. In some embodiments, the indium powder comprises 0.9-2.5% by mass. In some embodiments, the indium powder comprises 1-2.4% by mass. In some embodiments, the indium powder comprises 1.1-2.3% by mass. In some embodiments, the indium powder comprises 1.2-2.2% by mass. In some embodiments, the indium powder comprises 1.3-2.1% by mass. In some embodiments, the indium powder comprises 1.4-2% by mass. In some embodiments, the indium powder comprises 1.5-1.8% by mass. In some embodiments, the indium powder comprises 1.9-2% by mass.
[0038] In some embodiments, it is necessary to control the appropriate ball milling time so that indium is distributed as much as possible and as uniformly as possible on the surface of the porous silicon-carbon / porous carbon framework structure. By controlling the indium to be distributed as much as possible and as uniformly as possible on the surface of the porous silicon-carbon / porous carbon framework structure, uniform lithium electroplating can be guided, avoiding the nucleation and growth of lithium dendrites.
[0039] In some embodiments, the preset time for ball milling is 0.5-1.5 hours. In some embodiments, the preset time for ball milling is 0.6-1.4 hours. In some embodiments, the preset time for ball milling is 0.7-1.3 hours. In some embodiments, the preset time for ball milling is 0.8-1.2 hours. In some embodiments, the preset time for ball milling is 1 hour.
[0040] In some embodiments, if the indium powder particle size is too large, it can lead to uneven lithium deposition, causing localized lithium accumulation and subsequently resulting in the deposition and growth of lithium dendrites. Therefore, it is necessary to control the particle size of the indium powder.
[0041] In some embodiments, the indium powder has a particle size of less than 100 nm. In some embodiments, the indium powder has a particle size of less than 80 nm. In some embodiments, the indium powder has a particle size of less than 70 nm. In some embodiments, the indium powder has a particle size of less than 50 nm. In some embodiments, the indium powder has a particle size of less than 30 nm. In some embodiments, the indium powder has a particle size of less than 25 nm. In some embodiments, the indium powder has a particle size of less than 20 nm. In some embodiments, the indium powder has a particle size of less than 10 nm.
[0042] In some embodiments, physical vapor deposition can be used to heat metallic indium to evaporate it, and the indium vapor condenses on the surface of a porous carbon-silicon structure to form nanoscale indium powder. By controlling the deposition time and temperature gradient, the particle size of the indium powder can be controlled to be below 100 nm and approximately uniformly distributed on the surface of the porous carbon framework structure.
[0043] Step 130: Add binder and solvent, mix to form slurry, and stir the slurry.
[0044] Specifically, the ball-milled sample is ground into powder in a mortar and placed in a container (e.g., a beaker). A binder (e.g., PVDF) is then added, along with a suitable amount of solvent (e.g., N-methylpyrrolidone), allowing the solid and liquid components to mix and form a slurry. Further, the mixture is stirred with a magnetic stirrer for a certain time (1 hour) until homogeneous.
[0045] To ensure good bonding without affecting the electrical properties of the negative electrode material, the proportion of binder added needs to be controlled.
[0046] In some embodiments, the adhesive comprises 0.3%-0.8% by mass. In some embodiments, the adhesive comprises 0.4%-0.7% by mass. In some embodiments, the adhesive comprises 0.5%-0.6% by mass. In some embodiments, the adhesive comprises 0.5% by mass.
[0047] Step 140: The stirred slurry is coated onto the substrate and dried to obtain the silicon-carbon composite anode material.
[0048] Specifically, the stirred slurry is coated onto a substrate (e.g., copper foil) using a doctor blade (e.g., a 100 μm thick doctor blade). Further, the solvent in the slurry is removed by a drying process (e.g., drying in a drying oven) to obtain the prepared silicon-carbon composite anode material.
[0049] In some embodiments, during the drying process, it is necessary to control a suitable temperature to evaporate the solvent and to control the indium element to be approximately uniformly distributed on the surface of the porous silicon carbon structure as much as possible.
[0050] In some embodiments, the drying temperature is 100-160°C. In some embodiments, the drying temperature is 100-150°C. In some embodiments, the drying temperature is 110-150°C. In some embodiments, the drying temperature is 120-140°C.
[0051] The above preparation method can yield a high-performance silicon-carbon composite anode material. In this silicon-carbon composite anode material, silicon particles fill the pores of the porous carbon framework structure, and indium powder is approximately uniformly distributed on the surface of the porous carbon framework structure. The porous carbon framework structure, silicon particles, and indium powder form a porous three-dimensional hybrid electron-ion conductor (MIEC) network.
[0052] Indium's high ductility endows this silicon-carbon composite anode material with higher lithium diffusion and strain tolerance, enabling it to better withstand volume expansion and contraction during repeated cycling. Simultaneously, rapid lithium transport effectively suppresses dendrite formation and deposition, thereby improving the anode's cycle stability. Furthermore, indium is enriched at the porous interface, and its high lithium affinity promotes uniform lithium nucleation at the porous framework interface, redistributing electrochemical deposition to prevent localized lithium accumulation. The highly mechanically tough indium-rich interface also mitigates stress accumulation during lithiation / delithiation, maintaining interfacial consistency between the electrode and electrolyte. These synergistic effects effectively decouple the stress-dendritic interaction that plagues traditional silicon-based anodes.
[0053] Furthermore, the porous carbon framework structure provides stable electron transport channels, silicon particles serve as the primary active material for lithium-ion storage, while indium powder significantly improves the material's conductivity and lithium-ion transport efficiency. This three-dimensional MIEC network structure enables rapid electron and lithium-ion transport within the material, enhancing the electrode material's cycle stability and rate performance.
[0054] Example 1
[0055] Porous silicon carbon was prepared by placing a porous carbon framework structure within a reaction chamber using chemical vapor deposition (CVD). SiH4 gas was introduced as the silicon source, causing silicon atoms to deposit and grow within the pores of the porous carbon framework. By controlling the reaction temperature and time, silicon particles with a diameter of approximately 100 nm were obtained. These silicon particles were distributed in roughly uniform clusters within the pores of the porous carbon framework.
[0056] Porous silicon carbide and indium powder were mixed in a 50:1 ratio and stirred until homogeneous. The indium powder had a particle size of approximately 50 nm. The homogeneous mixture was then added to a ball mill and ball-milled for 1 hour.
[0057] The ball-milled sample was ground into powder in a mortar and placed in a beaker. PVDF binder was then added, along with a suitable amount of N-methylpyrrolidone as a solvent, allowing the solid and liquid components to mix and form a slurry. The mass percentage of the PVDF binder was 0.5%. The mixture was then stirred with a magnetic stirrer for 1 hour until homogeneous.
[0058] The stirred slurry was coated onto copper foil using a 100 μm thick doctor blade. Further, the slurry was dried in a drying oven to remove the solvent, yielding the prepared silicon-carbon composite anode material. The drying temperature was 150℃.
[0059] Figure 2 This is a SEM image of the silicon-carbon composite anode material described in the embodiments of this specification. Figure 2 As shown, silicon particles fill the pores of the porous carbon skeleton, while indium powder is dispersed on the surface of the porous carbon skeleton structure.
[0060] According to the battery design requirements, large-format electrode sheets are cut to sizes suitable for individual battery cells or battery packs. During cutting, it is essential to ensure neat edges to avoid internal short circuits or poor contact within the battery.
[0061] A composite cathode was prepared by mixing a positive electrode material (e.g., LiCoO2) with a sulfide electrolyte Li6PS5Cl at a mass ratio of 7:3 and grinding the mixture. The composite cathode was then used as the positive electrode in an all-solid-state battery, with Li6PS5Cl as the electrolyte and the prepared silicon-carbon composite negative electrode as the negative electrode. A full cell was assembled and tested.
[0062] Figure 3 This compares the electrochemical performance test results of existing silicon-carbon anode materials and the silicon-carbon composite anode materials described in the embodiments of this specification when applied to solid-state lithium batteries. Figure 3 As shown, the lithium-ion battery using the silicon-carbon composite anode described in the embodiments of this specification retains 100% of its capacity after 500 cycles, demonstrating excellent cycle stability and high-efficiency charge-discharge capability. In contrast, the capacity of a conventional lithium-ion battery using a conventional silicon-carbon anode rapidly decays to 67% after 500 cycles.
[0063] Figure 4 This is a comparison of cross-sectional SEM images of existing silicon-carbon anode materials and the silicon-carbon composite anode materials described in the embodiments of this specification when applied to solid-state lithium batteries. Figure 5 This is a top-view SEM image comparison of existing silicon-carbon anode materials and the silicon-carbon composite anode material described in the embodiments of this specification when applied to solid-state lithium batteries. Figure 4 and Figure 5As shown, conventional silicon-carbon anodes generate lithium dendrites during long-term cycling, and due to the lack of a robust ion conduction network, significant lithium dendrite proliferation and localized stress accumulation occur. However, in the silicon-carbon composite anode of the embodiments in this specification, the MIEC network constructed from indium and porous silicon-carbon materials promotes rapid lithium-ion transport, effectively suppressing dendrite formation and thus reducing stress-induced damage to the anode.
[0064] This specification also provides a silicon-carbon composite anode material, which includes a porous carbon framework structure, silicon particles filling the pores of the porous carbon framework structure, and indium powder approximately uniformly distributed on the surface of the porous carbon framework structure. The silicon particles have a particle size of 5-200 nm, and the indium powder has a particle size of less than 100 nm. The porous carbon framework structure, silicon particles, and indium powder form a porous three-dimensional hybrid electron-ion conductor network.
[0065] This specification also provides a solid-state battery, which includes the silicon-carbon composite anode material described above.
[0066] It should be noted that the above embodiments are only used to illustrate the technical solutions of this specification, and are not intended to limit them. Although this specification has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this specification.
[0067] Furthermore, unless expressly stated in the claims, the order of processing elements and sequences, the use of numbers and letters, or other names described in this specification are not intended to limit the order of the processes and methods described herein. Although various examples have been discussed in the foregoing disclosure of some embodiments of the invention that are currently considered useful, it should be understood that such details are for illustrative purposes only, and the appended claims are not limited to the disclosed embodiments; rather, the claims are intended to cover all modifications and equivalent combinations that conform to the spirit and scope of the embodiments described herein. For example, while the system components described above can be implemented using hardware devices, they can also be implemented solely using software solutions, such as installing the described system on existing servers or mobile devices.
[0068] Similarly, it should be noted that, in order to simplify the description disclosed herein and thus aid in the understanding of one or more embodiments of the invention, the foregoing description of embodiments in this specification may sometimes combine multiple features into a single embodiment, drawing, or description thereof. However, this method of disclosure does not imply that the subject matter of this specification requires more features than those mentioned in the claims. In fact, the embodiments contain fewer features than all the features of a single embodiment disclosed above.
[0069] In some embodiments, numbers describing the quantity of components and attributes are used. It should be understood that such numbers used in the description of embodiments are modified in some examples with the terms "approximately," "approximately," or "generally." Unless otherwise stated, "approximately," "approximately," or "generally" indicates that the numbers are allowed to vary by ±20%. Accordingly, in some embodiments, the numerical parameters used in the specification and claims are approximate values, which may be changed depending on the characteristics required by individual embodiments. In some embodiments, numerical parameters should take into account specified significant digits and employ a general method of digit reservation. Although the numerical ranges and parameters used to confirm their breadth of range in some embodiments of this specification are approximate values, in specific embodiments, such values are set as precisely as feasible.
[0070] For each patent, patent application, patent application publication, and other material, such as articles, books, specifications, publications, and documents, referenced in this specification, the entire contents of which are incorporated herein by reference. This excludes historical application documents that are inconsistent with or conflict with the content of this specification, as well as documents that limit the broadest scope of the claims in this specification (currently or subsequently appended to this specification). It should be noted that in the event of any inconsistency or conflict between the descriptions, definitions, and / or terminology used in the supplementary materials to this specification and the content of this specification, the descriptions, definitions, and / or terminology used in this specification shall prevail.
[0071] Finally, it should be understood that the embodiments described in this specification are merely illustrative of the principles of the embodiments described herein. Other variations may also fall within the scope of this specification. Therefore, alternative configurations of the embodiments described herein are intended to be illustrative rather than limiting, and should be considered consistent with the teachings of this specification. Accordingly, the embodiments described herein are not limited to those explicitly introduced and described herein.
Claims
1. A silicon-carbon composite anode material, characterized in that, The negative electrode material includes: Porous carbon framework structure; Silicon particles fill the pores of the porous carbon framework structure; Indium powder is approximately uniformly distributed on the surface of the porous carbon framework structure.
2. The negative electrode material as described in claim 1, characterized in that, The silicon particles have a particle size of 5-200 nm.
3. The negative electrode material as described in claim 1, characterized in that, The indium powder has a particle size of less than 100 nm.
4. The negative electrode material as described in claim 1, characterized in that, The porous carbon framework structure, the silicon particles, and the indium powder form a porous three-dimensional hybrid electron-ion conductor (MIEC) network.
5. A method for preparing a silicon-carbon composite anode material, used to prepare the anode material as described in any one of claims 1-4, characterized in that, The method includes: Porous silicon carbon is prepared based on a porous carbon framework and a silicon source, wherein silicon particles are filled in the porous carbon framework. The porous silicon carbide and indium powders are mixed in a preset ratio and then stirred. Add binder and solvent, mix to form a slurry, and then stir the slurry. The stirred slurry is coated onto a substrate and then dried to obtain the silicon-carbon composite anode material.
6. The preparation method according to claim 5, characterized in that, The indium powder accounts for 0.5-3% of the total mass.
7. The preparation method according to claim 5, characterized in that, After mixing and stirring the porous silicon carbide and the indium powder, the process further includes: The ball milling process is performed for a preset time, which is 0.5-1.5 hours.
8. The preparation method according to claim 5, characterized in that, The drying process is carried out at a temperature of 100-160℃.
9. The preparation method according to claim 5, characterized in that, The adhesive comprises 0.3%-0.8% by mass.
10. A solid-state battery, characterized in that, The solid-state battery includes the silicon-carbon composite anode material as described in any one of claims 1-4.